The Association of Glycemic Gap with Cognitive Function After Ischemic Stroke or Transient Ischemic Attack - Min Y; Xu Q; Wang Y; Li Z (Neuropsychiatric Disease and Treatment)
Yan Min,1 Qin Xu,1,2 Yongjun Wang,1– 3 Zixiao Li1,2,4 1Department of Neurology, Beijing TianTan Hospital, Capital Medical University, Beijing, People’s Republic of China; 2China National Clinical Research Center for Neurological Diseases, Beijing, People’s Republic of China; 3Center of Stroke, Beijing Institute for Brain Disorders, Beijing, People’s Republic of China; 4Chinese Institute for Brain Research, Beijing, People’s Republic of ChinaCorrespondence: Yongjun Wang, Beijing TianTan Hospital, Capital Medical University, Beijing, People’s Republic of China, Tel +86 010 59978351, Email yongjunwang@ncrcnd.org.cn Zixiao Li, Beijing TianTan Hospital, Capital Medical University, Beijing, People’s Republic of China, Tel +86 010 59978351, Email lizixiao2008@hotmail.comBackground: Glycemic gap (GG), as a measure of an acute derangement in glucose level in response to an active disease state, has been found to be associated with adverse outcomes in many diseases. This study aimed to determine the relationship of GG with cognitive function after ischemic stroke or transient ischemic attack (TIA).Methods: Patients included were enrolled from a subgroup of China National Stroke Registry-III (CNSR-III). Cognitive function was assessed by the Beijing edition of the Montreal cognitive assessment (MoCA) scale. Post-stroke cognitive impairment (PSCI) was diagnosed as a MoCA score≤ 22. Post-stroke cognitive decline (PSCD) was defined as a decrease of > 2 points on the MoCA score between the 3-month and 1-year assessments. GG was calculated using admission blood glucose minus hemoglobin A1c-derived average blood glucose. Multivariable logistic regression analysis was used to evaluate the correlation between GG and cognitive function.Results: We enrolled 767 patients with a median age of 60 years old, including 247 (32.2%) patients with PSCI in 3 months, 228 (29.73%) with PSCI in 1 year, and 166 (21.64%) patients with PSCD. The highest GG levels were related to PSCI in 3 months after adjusted for multiple potential confounders (adjusted odd ratio (OR): 2.021, 95% CI: 1.055– 3.869, P=0.0338), but not in patients with PSCI in 1 year or PSCD. No significant interactions for the impact on PSCI were observed in subgroups (P interaction > 0.05 for all).Conclusion: Our findings show that GG is associated with acute post-stroke cognitive impairment, but not with the long-term cognitive impairment or cognitive decline.Keywords: cognitive function, glycemic gap, stroke, transient ischemic attack